Analisis Pengaruh Penggunaan Artificial Intelligence (AI) Dalam Pengerjaan Tugas Kuliah Mahasiswa Pendidikan Teknik Elektro - Hidayatullah, Syarif; Effendi, Hansi (Jurnal Pendidikan Teknik Elektro, 2025)
This research explores the role of Artificial Intelligence (AI) in assisting Electrical Engineering students with their coursework. Using a quantitative approach, the study surveyed a sample of 167 students to analyze the extent to which Artificial Intelligence (AI) contributes to the efficiency of completing assignments. The data was processed using a descriptive analysis method to provide a clear understanding of the patterns and trends in AI utilization among students. The findings indicate that AI has a significant influence, accounting for 56% of the effectiveness in completing coursework. This suggests that students who frequently use AI tools tend to complete their assignments more efficiently. The study highlights that the integration of AI can enhance productivity, reduce the time required to solve complex problems, and improve overall academic performance. These results underscore the growing importance of AI in education, particularly in technical fields such as Electrical Engineering, where problem-solving and computational tasks play a crucial role in students’ learning processes.